2015
DOI: 10.1002/hyp.10577
|View full text |Cite
|
Sign up to set email alerts
|

Identifying run‐off contributions during melt‐induced run‐off events in a glacierized alpine catchment

Abstract: We analysed contributions to run‐off using hourly stream water samples from seven individual melt‐induced run‐off events (plus one rainfall event) during 2011, 2012 and 2013 in two nested glacierized catchments in the Eastern Italian Alps. Electrical conductivity and stable isotopes of water were used for mixing analysis and two‐component and three‐component hydrograph separation. High‐elevation snowmelt, glacier melt and autumn groundwater were identified as major end‐members. Discharge and tracers in the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 73 publications
16
91
1
Order By: Relevance
“…The increase in discharge coincides with decreasing streamflow δ 18 O during the early melt event (Fig. 4a and c) and confirms the earlier findings of Engel et al (2016), who identified inverse relationships between streamflow δ 18 O and discharge during several 24 h events in an adjacent valley on the southern side of the main Alpine ridge, although their findings rely on streamflow contributions from snow and glacier melt. The lower stream water isotopic composition during peak melt suggests a remarkable contribution of more depleted snowmelt to streamflow and therefore confirms the results of the IHS.…”
Section: Temporal Variation In Streamflow During the Melting Seasonsupporting
confidence: 90%
See 3 more Smart Citations
“…The increase in discharge coincides with decreasing streamflow δ 18 O during the early melt event (Fig. 4a and c) and confirms the earlier findings of Engel et al (2016), who identified inverse relationships between streamflow δ 18 O and discharge during several 24 h events in an adjacent valley on the southern side of the main Alpine ridge, although their findings rely on streamflow contributions from snow and glacier melt. The lower stream water isotopic composition during peak melt suggests a remarkable contribution of more depleted snowmelt to streamflow and therefore confirms the results of the IHS.…”
Section: Temporal Variation In Streamflow During the Melting Seasonsupporting
confidence: 90%
“…At the event-scale comparable studies are rare. Engel et al (2016) report a maximum daily snowmelt contribution estimated with a three-component hydrograph separation of 33 % for an 11 km 2 southwest of the Rofen valley with similar physiographic characteristics, but on the southern side of the main Alpine ridge. It should be mentioned that in their study, runoff was fed by three components (snowmelt, glacier melt, and groundwater) and lower snowmelt contributions were prevalent because most of the catchment area (69 %) was snow free.…”
Section: Hydrograph Separation Results and Inferred Runoff Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…For consistency, sampling was carried out during the same time interval defined from 12 am to 4 pm. Previous measurements showed that the main melt water contribution was from snow in June and July (recent and old snowmelt, respectively), from glacier ice in August and from rainfall in September [25]. Therefore, the assumption that a single day is representative of the monthly scale is legitimate.…”
Section: Study Site and Samplingmentioning
confidence: 99%